Mathematical Modeling of Green Sea Turtle Population Dynamics Under Environmental and Thermal Constraints (CSIAM Transactions on Life Sciences, 2026)
Global warming and deteriorating environmental conditions have raised concerns about the persistence of green sea turtle populations, whose reproduction is governed by temperature-dependent sex determination. This study employs mathematical modeling to investigate these ecological challenges. Building on our previous models of green sea turtle population dynamics, we develop a sex-structured and stage-structured life history model that integrates temperature-dependent sex determination and ecological viability, offering a mechanistic framework for understanding green sea turtle population dynamics under climate and environmental stress. Our findings reveal that population dynamics are governed by an Allee-adjusted reproductive number, which accounts for both thermal and environmental influences. Additionally, we conduct a global stability analysis of the collapsed equilibrium using the singular perturbation approach, offering insights into long-term population viability. While additional parameter validation is necessary for definitive conclusions, our results illustrate how climate change and deteriorating environmental conditions shape the long-term viability of green sea turtle populations.
Keywords: Temperature-dependent sex determination; green sea turtle; sex-structured and stage-structured; Allee effects; population collapse; bi-stability